Physical and mechanical properties of sugar palm/glass fiber reinforced thermoplastic polyurethane hybrid composites - Atiqah Afzaluddin; Mohammad Jawaid; Mohd Sapuan Salit; Mohamed Ridwan Ishak (Journal of Materials Research and Technology, 2019)
This paper studied the physical and mechanical properties of sugar palm and glass fiber reinforced thermoplastic polyurethane hybrid composites with the aim of investigation on the hybrid effects of the composites made of natural and synthetic fibers. The aim of this study is to evaluate the physical properties such as density, thickness swelling, water absorption whereas the tensile, flexural and impact properties of sugar palm, hybrid and glass composites were also investigated. Morphological properties of tensile fracture samples of composites were done by using scanning electron microscopy (SEM). The composites were fabricated at a constant weight fraction of total fiber loading at 40 wt.% using melt compounding method. The result revealed that incorporation of glass fiber 30 wt.% to sugar palm/TPU composites exhibited the higher density, lower thickness swelling and water absorption properties. The tensile and impact properties of the hybrid composites were improved with the increasing of sugar palm fiber content (30/10 SP/G) as compared to glass fiber reinforced composites (0/40 SP/G) due to the excellent hybrid performance of the two fibers. The flexural properties were increased when the higher amount of glass fiber was introduced at 40 wt.% (0/40 SP/G). The fibers cracks, fiber pull out and fiber dislocation of the fractured surfaces are evaluated by using scanning electron microscope (SEM). Overall results indicated that the incorporation of glass fiber to sugar palm fiber composites can improve the physical and mechanical properties and developed hybrid composites can be used as an alternate material for glass fiber reinforced polymer composites for different applications. Keywords: Sugar palm fibers, Thermoplastic polyurethane, Glass fibers, Hybrid composites, Physical properties, Mechanical properties